Experiences of including costs of added life years in health economic evaluations in Sweden - Pirhonen, Laura; Davidson, Thomas (Farmeconomia. Health Economics and Therapeutic Pathways, 2014)
It is of importance to include the appropriate costs and outcomes when evaluating a health intervention. Sweden is the only country where the national guidelines of decisions on reimbursement explicitly state that costs of added life years should be accounted for when presenting health economic evaluations. The aim of this article is to, from a theoretical and empirical point of view, critically analyze the Swedish recommendations used by the Dental and Pharmaceutical Benefits Agency (TLV), when it comes to the use of costs of added life years in economic evaluations of health care. The aim is furthermore to analyze the numbers used in Sweden and discuss their impact on the incremental cost‑effectiveness ratios of assessed technologies. If following a societal perspective, based on welfare economics, there is strong support for the inclusion of costs of added life years in health economic evaluations. These costs have a large impact on the results. However this fact may be in conflict with ethical concerns of allocation of health care resources, such as favoring the younger part of the population over the older. It is important that the estimates of production and consumption reflect the true societal values, which is not the case with the values used in Sweden.